(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
Currently, classrooms have had various advances in the way of teaching. However, assertive communication has been ignored to work on healthy and peaceful coexistence. Assertive communication has been included as one of the key social skills in the teaching, learning and prevention of psychosocial problems. This article aims to analyze the incidence of assertive communication in the construction of peace class- rooms, with an investigation using documentary review methods, analysis and synthesis of information, delimiting the population among the last school grades obtaining as a result the need to use assertive two- way communication in a daily practice under the use of constructivist models, promoting the development of critical, creative, reflective and investigative skills, allowing students to promote activities that promote critical thinking using their capacities in the processes of peace building.